Low-dose titrated amitriptyline as second-line treatment for adults with irritable bowel syndrome in primary care: the ATLANTIS RCT - Wright-Hughes, Alexandra; Ford, Alexander C; Alderson, Sarah L; Ow, Pei Loo; Ridd, Matthew J; Foy, Robbie; Bishop, Felicity L; Chaddock, Matthew; Cook, Heather; Cooper, Deborah; Fernandez, Catherine; Guthrie, Elspeth A; et al. (Health technology assessment (Winchester, England), 2024)
Irritable bowel syndrome, characterised by abdominal pain and a change in stool form or frequency, is most often managed in primary care. When first-line therapies are ineffective, National Institute for Health and Care Excellence guidelines suggest considering low-dose tricyclic antidepressants as second-line treatment, but their effectiveness in primary care is unknown and they are infrequently prescribed by general practitioners. To evaluate the clinical and cost-effectiveness of low-dose titrated amitriptyline as a second-line treatment for irritable bowel syndrome in primary care. A pragmatic, randomised, multicentre, two-arm, double-blind, placebo-controlled trial. A nested, qualitative study explored participant and general practitioner experiences of treatments and trial participation, and implications for wider use of amitriptyline for irritable bowel syndrome in primary care. Participants, clinicians, investigators and analysts were masked to allocation. Fifty-five general practices in three regions in England (Wessex, West of England, West Yorkshire). Patients aged ≥ 18 years meeting Rome IV criteria for irritable bowel syndrome with ongoing symptoms after trying first-line treatments and no contraindications to TCAs. Amitriptyline 10 mg once-daily, self-titrated by participants to a maximum of 30 mg once-daily or matched placebo for 6 months. Participants randomised 1 : 1 with most having the option to continue blinded treatment for a further 6 months. The primary participant-reported outcome was the effect of amitriptyline on global irritable bowel syndrome symptoms at 6 months, measured using the irritable bowel syndrome Severity Scoring System, with a 35-point between-group difference defined as the minimum clinically important difference. The key secondary outcome was the proportion of participants reporting subjective global assessment of relief at 6 months, defined as somewhat, considerable, or complete relief of symptoms. Other secondary outcomes included: effect on global symptoms, via the irritable bowel syndrome Severity Scoring System, and subjective global assessment of relief of irritable bowel syndrome symptoms at 3 and 12 months; effect on somatic symptom-reporting at 6 months; anxiety an-d depression scores; ability to work and participate in other activities at 3, 6 and 12 months; acceptability, tolerability and adherence to trial medication. Four hundred and sixty-three participants were randomised to amitriptyline (232) or placebo (231). An intention-to-treat analysis of the primary outcome showed a significant difference in favour of amitriptyline for irritable bowel syndrome Severity Scoring System score between arms at 6 months [-27.0, 95% confidence interval (CI) -46.9 to -7.10; = 0.008]. For the key secondary outcome of subjective global assessment of relief of irritable bowel syndrome symptoms, amitriptyline was superior to placebo at 6 months (odds ratio 1.78, 95% CI 1.19 to 2.66; = 0.005). Amitriptyline was superior to placebo across a range of other irritable bowel syndrome symptom measures but had no impact on somatoform symptom-reporting, anxiety, depression, or work and social adjustment scores. Adverse event trial withdrawals were more common with amitriptyline (12.9% vs. 8.7% for placebo) but most adverse events were mild. The qualitative study thematically analysed 77 semistructured interviews with 42 participants and 16 GPs. Most participants found the self-titration process acceptable and empowering. General practitioners should offer low-dose amitriptyline to patients with irritable bowel syndrome whose symptoms do not improve with first-line therapies. Guidance and resources should support GP-patient communication to distinguish amitriptyline for irritable bowel syndrome from use as an antidepressant and to support patients managing their own dose titration. This trial is registered as ISRCTN48075063. This award was funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme (NIHR award ref: 16/162/01) and is published in full in Vol. 28, No. 66. See the NIHR Funding and Awards website for further award information.